Contribution of Microorganisms to Biogenic Amine Accumulation during Fish Sauce Fermentation and Screening of Novel Starters - Xinxiu Ma (MDPI AG, 2021)
In this study, high-throughput sequencing and culture-dependent and HPLC methods were used to investigate the contribution and regulation of biogenic amines (BAs) by dominant microorganisms during fish sauce fermentation. The results showed that the microbial composition constantly changed with the fermentation of fish sauce. Tetragenococcus (40.65%), Lentibacillus (9.23%), Vagococcus (2.20%), Psychrobacter (1.80%), Pseudomonas (0.98%), Halomonas (0.94%) and Staphylococcus (0.16%) were the dominant microflora in fish sauce. The content of BAs gradually increased as the fermentation progressed. After 12 months of fermentation, the histamine content (55.59 mg/kg) exceeded the toxic dose recommended by the Food and Drug Administration (FDA). Correlation analysis showed that dominant microorganisms have a great contribution to the accumulation of BAs. By analyzing the BA production capacity of dominant isolates, the accumulation of BAs in fish sauce might be promoted by Tetragenococcus and Halomonas. Moreover, four strains with high BA reduction ability were screened out of 44 low BA-producing dominant strains, and their influence on BA accumulation in fermented foods was determined. Results demonstrated that Staphylococcus nepalensis 5-5 and Staphylococcus xylosus JCM 2418 might be the potential starters for BA control. The present study provided a new idea for the control of BAs in fermented foods.